Optimization and economic analysis of a solar assisted heat pump drying system - Hawlader, Mohammad Nurul Alam; Rahman, S. M. A.; Jahangeer, K. A. (IIUM Press, 2011)
A solar assisted heat pump drying system has been designed, fabricated and tested. The performance of the system has been investigated under the meteorological conditions of Singapore. This paper presents an economic optimization of a solar assisted heat pump drying system. Economic viability of solar energy heating systems is usually made by comparing the cost flows recurring throughout the lifetime of the solar and conventional alternative systems. Therefore, the optimum variables by using simulation program and pay back period of the system are presented in this paper. Effect of load and different economic variables on pay back period is also investigated. From optimization, it was found that the optimum combination of air collector area, evaporator collector area, drying temperature, and air mass flow rate are about 1.25 m2, 2 m2, 500C and 0.036 kg/sec, respectively, which provides around 90% of the total load. Economic analysis shows that system has a sufficient amount of savings during the life cycle with a minimum payback period of about 4.37 year.